1864 Terr. of Mont. Acts 182 - (:unkn) unknown (My University, 1864)
§ 35: Prohibited dueling and killing a person with a rifle, shotgun, pistol, Bowie knife, dirk, small sword, backsword, or other dangerous weapon. Violators guilty of murder in the first degree.
Keywords: DUELING